Arbitraż w posttotalitarnych czasach PRL — uwagi wybrane na tle zakresu podmiotowego dopuszczalności arbitrażu (dawny art. 697 § 3 i 4 k.p.c.) - Budniak-Rogala, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This elaboration is an attempt to introduce an interpretation of former Art. 697 § 3 and 4 of the Civil Procedure Code regarding admissibility of concluding agreements for submitting disputes to an arbitration court by social economy entities. The analyzed provisions provided relevant limitations of the objective scope of admissibility of arbitration regarding said social economy entities – both in domestic and international transactions. It involved especially with the establishment of the State Economic Arbitral Institution. The solutions adopted by the legislator were undoubtedly the result of applying the principles of the socio-economic regime of the post-totalitarian Polish People’s Republic.
Keywords: zakres dopuszczalności arbitrażu; podmiotowy zakres dopuszczalności arbitrażu; zdolność arbitrażowa; jednostki gospodarki uspołecznionej; sądownictwo polubowne w czasach PRL